Association of anti-phospholipid antibodies and hepatitis B virus infection in Najaf Governorate - Ameer Mohammed Kadhim; Hawraa Ameer Mubark; Dhefaf Hameed Al-Mudhafar; Zainab Hayder Abdulmajeed (Medical Journal of Babylon)
Abstract Background: Antiphospholipid syndrome (APS) is an autoimmune disease with multifactorial risk factors including genetic and environmental factors such as viral infection, and it can be diagnosed by the presence of antiphospholipid antibodies (APLA) in the serum. Hepatitis B virus (HBV) is one of the most prevalent viral infections in the world and has been connected to a number of autoimmune illnesses. Some studies suggested that HBV might be the cause of APLA production and APS development. No previous study was done in Iraq regarding the relationship between these two. Objective: To estimate the prevalence of APLA in HBV-infected individuals in Najaf. Materials and Methods: A cross-sectional study was done in Najaf from September 2022 to March 2023, and it included 113 patients (70 were males, age range was 15–85 years) with HBV infection and without any history of APS. They were tested for Hepatitis B core (HBc) total and immunoglobulin M (IgM) Abs and then tested for APLA by enzyme-linked immunosorbent assay (ELISA) technique. The Statistical Program for Social Sciences (SPSS) version 26.0 was used for statistical analysis. Results: Only four patients were positive for HBc total and IgM the remaining 109 were positive for IgG only, 38 (33.63%) were positive for APLA, and the age group (41–50 years) with the highest rate of APLA positivity. Non-significant statistical difference was seen between APLA and gender or age. Acute HBV had higher titers of APLA. Conclusion: HBV may lead to the production of APLA in some patients without any other risk factors, especially in middle-aged patients.